Challenges and Solutions in Teaching Arabic Grammar: Pedagogical and Cultural Perspectives - Khitam, Achmad Khusnul (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
It is well known that the issue of teaching Arabic language remains essential, not only for non-native speakers but also for native speakers' children alike. As for grammar, it is more challenging to teach and comprehend due to its numerous rules interconnected with each other. Students often claim difficulty in understanding these complex rules, exacerbated by teachers' inadequate application of effective teaching methods. This research aims to explore the teaching of grammar rules, discussing the problems encountered by students in learning them and suggesting solutions, alongside a concise explanation of the essence of grammar education. This study is a qualitative conceptual research using a structural educational approach and based on library research. The data consist of classical and modern grammar books, teaching materials, and academic articles. Findings indicate that students’ aversion to Arabic grammar stems from multiple factors, including the abstract nature of grammar, inconsistent pedagogical strategies, the rigidity of traditional textbooks, and limited contextualization of grammatical examples. The proposed solution for both students and teachers involves increasing practice, clarifying and simplifying grammar, among other strategies. Keywords – Arabic, Problems, Solution, Teaching.